Peningkatan Produktivitas Melalui Perbaikan Sistem Budidaya Padi Sawah Di Tengah Ancaman Perubahan Iklim - Joko Pramono; Anggi Sahru Romdon (Program Studi Agribisnis Universitas Sumatera Selatan, 2022)
The demand for food is increasing at the same rate as the population. The government continues its efforts to increase the availability of staple foods, particularly rice, despite the threat of climate anomalies and the shrinking of paddy fields. Adaptive rice cultivation technology innovations are strongly encouraged to continue to be developed on a large scale. Application of the jajar legowo planting system in conjunction with other technological components, such as the use of varieties that are flood-tolerant, drought-tolerant, and early maturing, as well as water-saving irrigation technology, can increase rice yield. The increased productivity resulting from the implementation of jajar legowo varies between 14.7% and 21.3% across regions. Improved climate-change-adapted varieties can boost yield by up to 28%. Some efforts to eliminate the negative impacts of climate change in the agricultural sector are; i) utilizing climate change information and planting calendar information to determine planting time and the commodities; ii) selecting and developing plant species and varieties that are adaptive to climate change, including varieties that are drought tolerant, inundated tolerant, and tolerant of salinity, as well as early-aged varieties to develop climate-adaptive cropping patterns; iii) applying water-saving technologies such as intermittent irrigation systems; iv) developing soil and plant management technologies to increase plant adaptabilities such as adding organic material and biochar application; v) developing crop-livestock systems to reduce risk and optimize the use of land resources; and vi) utilizing farm protection facilities such as farming insurance (Asuransi Usaha Tani Padi/AUTP) as part of mitigation efforts.